Study of the Provision of Construction Facilities with Management Personnel - Usmanov Ilhom Achilovich (International Journal on Orange Technologies, 2021)
This article is devoted to the impact of personnel policy on the rating of construction organizations. The authors carried out a sample survey of construction projects in the city of Samarkand for the provision of management personnel. The presence of objective factors that hinder the improvement of the rating of small construction organizations is shown.